Reduksi Osilasi Daya Pada MPPT Panel Surya Dengan Metode Kombinasi PNO dan Fuzzy - Suriadi Suriadi; Intan Nurul Fajri; Rizal Munadi; Mansur Gapy (Universitas Syiah Kuala, 2019)
Solar panels are an essential part of a system of electrical source devices that receives light energy to be processed into electrical energy with direct current (DC) output. The main problem in the use of solar panels is that the production of power in solar panels is not constant due to the temperature and solar radiation changes. This non-constant power causes the solar panel output power to fluctuate and become unstable. This output power will be used in processing using the MPPT Perturb and Observe (PNO) method to obtain the maximum solar panel receiving point. This PNO method uses two input parameters and can be applied to all types of solar panels. This study aims to reduce the oscillation of the output power of MPPT using electronic power simulations on a three-level boost converter by combining PNO and Fuzzy MPPT methods. The Fuzzy method in this study uses the Mamdani inference method, which uses two inputs and one output. The boost converter was tested using a simulation on several conditions of sunlight received by solar panels. The simulation results show that the power output from the MPPT PNO and Fuzzy methods can reduce oscillation more optimally, 78.57%.